Applied learning - the use of timber in architectural education - Fereday, George (Compelo Ltd, 2018)
The CASS School of Architecture at London Metropolitan University conducts a week long making workshop with its second year undergraduate architecture students on an annual basis. The intention is that the students learn through applied making experiences at the building scale using timber and other natural materials. This article for the Timber Trade Journal summarises the applied learning techniques used in 2018.